Role of weight-adjusted waist circumference index and non-high-density lipoprotein cholesterol/high-density lipoprotein cholesterol ratio in prediabetes risk: A mediation analysis - Wei Mi; Cuixiao Wang (PLoS ONE, 2025)
Objective This study aims to investigate the prevalence of prediabetes among U.S. adults using NHANES 2017–2023 data, explore the relationship between the weight-adjusted waist circumference index (WWI) and the non-high-density lipoprotein cholesterol/high-density lipoprotein cholesterol ratio (NHHR) and the risk of prediabetes, and provide a theoretical foundation for the early identification and intervention of prediabetes. Methods Logistic regression, linear regression model, subgroup analysis, restricted cubic spline (RCS) analysis, and mediation analysis were employed to examine the effect of WWI on prediabetes and the mediating role of NHHR. Results A total of 9,713 adults were included in the analysis, with an age range of 20–80 and a mean age of 51.26 ± 17.25. Of these, 3,208 cases (33.03%) were prediabetic. The adjusted model showed that WWI (OR = 1.55, 95% CI: 1.46, 1.64) may increase the probability of prediabetes. The results of subgroup analysis, stratified by factors such as gender and age, largely supported these findings. The adjusted model also indicated that NHHR (OR = 1.20, 95% CI: 1.16, 1.25) may increase the probability of prediabetes. The RCS analysis revealed a nonlinear relationship between both WWI and NHHR with the risk of prediabetes. Further mediation analysis indicated that NHHR mediated 10% of the effect of WWI on prediabetes. Conclusion WWI and NHHR were significantly associated with the risk of prediabetes, and NHHR partially mediated the effect of WWI on prediabetes. This study provides a new theoretical basis for early prediabetes screening, prevention, and control. In the future, interventions targeting WWI and NHHR through lifestyle changes may be effective in preventing prediabetes.